Pengaruh Earnings Variability, Ukuran Perusahaan, Dan Negative Earnings Terhadap Biaya Utang - Adelia Suryani, Elsa Imelda, Henny Wirianata (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to analyze the effect of earnings variability, firm size, and negative earnings on cost of debt.This research is conducted by using 267 samples of manufacturing companies listed in Indonesia Stock Exchange in the period of 2015–2017,using purposive sampling method and processed with EViews 10 program. The result of partially test (t test) shows thatearnings variability, firm size, and negative earnings have significant effect on cost of debt. This study also shows that earnings variability, firm size, and negative earnings have a significant effect on cost of debt simultaneously